Isolasi Selulosa Dari Serat Buah Lontar (Borassus Flabellifer L.) Asal Pulau Timor Serta Aplikasinya Sebagai Bahan Baku Bioplastik - Anastasia Grandivoriana Nomi; Christin Hendriyani Bonnu; Marlon Jusak Rinaldy Benu Beno (Jurnal Penelitian Pertanian Terapan, 2026)
The increasing use of synthetic polymer-based plastics derived from non-renewable resources has caused serious environmental and health problems. Therefore, the development of bioplastics based on natural polymers is considered a sustainable solution. This study aimed to isolate cellulose from lontar fruit fiber (Borassus flabellifer Linn.) and to evaluate its potential application as a raw material for bioplastic production. Lontar fruit fiber was subjected to alkaline treatment using NaOH, followed by bleaching with H₂O₂ and acid hydrolysis using H₂SO₄. The isolated cellulose was characterized in terms of yield, moisture content, and functional group identification using Fourier Transform Infrared (FTIR) spectroscopy. The results showed that the final cellulose yield reached 45.67%, indicating the dominance of the cellulose fraction after significant removal of hemicellulose and partial lignin. FTIR analysis confirmed the presence of characteristic cellulose functional groups, including hydroxyl (–OH), C–H stretching, and β-1,4-glycosidic (C–O–C) bonds, while lignin-related absorption bands were observed with very low intensity. The isolated cellulose was subsequently applied in bioplastic formulation using gelatin and glycerol as plasticizers. The resulting bioplastic exhibited homogeneous appearance, good elasticity, and low brittleness. These findings demonstrate that cellulose derived from lontar fruit fiber has strong potential as an environmentally friendly bioplastic raw material and supports the valorization of local biomass waste from dryland ecosystems.